Proximate Characteristics and Digestibility of Protein in Mushroom Rendang Produced by Sterilization Using a Modified Pressure-Cooking Method - Rendri Yaswan; Novizar Nazir; Daimon Syukri (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Mushroom rendang is one of several plant-based ready-to-eat food alternatives with the potential to become a commercial product. However, the thermal sterilization process required to ensure food safety may potentially affect the product’s nutritional quality. This study aims to investigate changes in the proximate composition and protein digestibility of mushroom rendang following sterilization utilizing a modified pressure sterilization method. Samples were placed in retort pouches and sterilized in a modified pressure cooker for 50, 70, and 90 minutes after venting. Proximate analysis included moisture, ash, protein, fat, and carbohydrates, following AOAC methods. Protein digestibility was determined using an in vitro method. We examined the data using ANOVA and Duncan’s post-hoc test at a 95% confidence level. The results showed that sterilization time had a significant effect (p < 0.05) on several proximate parameters and protein digestibility. Moisture, protein, and fat levels decreased as sterilizing time rose, however, carbohydrate content increased correspondingly due to the moisture reduction. Protein digestibility increased with mild sterilization because protein denaturation improved enzyme access. Whereas it decreased with longer sterilization times due to the production of protein aggregates and Maillard reaction products. Concisely, sterilization using a modified pressure cooker produced mushroom rendang with consistently good nutritional characteristics and has the potential to serve as an economical alternative sterilization technology for small-scale food industries. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 12 Sustainable consumption and consumption